Коронация, или Последний из романов - Акунин Борис (Новый детективъ, 2008)
Экземпляры: (20170503) / Инвентарный номер: 35523 / Цена: 52.00 / Сис.шифр: Р2 / Авт.знак: А 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6